Clinical Implementation of Routine Screening for Fetal Trisomies in the UK NHS: Cell-Free DNA Test Contingent on Results From First-Trimester Combined Test. Issue 5 (May 2016) - Gil, M. M.; Revello, R.; Poon, L. C.; Akolekar, R.; Nicolaides, K. H.
Abstract : Abstracted from Ultrasound Obstet Gynecol 2016;47:45–52 Although detection of trisomies 21, 18, and 13 by cell-free DNA (cfDNA) analysis of maternal blood is superior to other methods of screening, it is expensive. To maximize performance at reduced cost, a strategy that can be used is to offer cfDNA testing contingent on the results of the first-trimester combined test that is used currently.